ANALISIS PENGARUH STRUKTUR KEPEMILIKAN, KINERJA KEUANGAN DAN RISIKO KEUANGAN TERHADAP MANAJEMEN LABA RIIL - Ellyne Ethica Sari; Triyono Triyono (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This purpose of this study analyzed the effect of Managerial Ownership Structure (SKM), Financian Performance (ROA), Financian Risk (RK) on Real Earnings Management. The study is based on secondary data from the annual financial statements on banking sub-sector companies listed on the Indonesia Stock Exchange for the period 2016-2020. The data are taken from the website.idx.co.id. Sampling method used purposive sampling and the analysis method used multiple regression. The result showed that the SKM and RK variables have no effect on Real Earnings Management while the ROA variable has a significant effect on Real Earnings Management. The implication result of this study was the possibility of earnings having low quality and encouraging earnings management.